Improving Transparency and Accountability in Public-Private Partnerships : Disclosure Diagnostic Report--Nigeria - World Bank Group (World Bank, Washington, DC, 2017)
A World Bank Public-Private Partnerships (PPP) team conducted a study in Nigeria between September 2016 and April 2017, using the PPP Disclosure Diagnostic template recommended by the World Bank's Framework for Disclosure of Information in PPPs. This study has been consolidated in the form of a PPP Disclosure Diagnostic Report for Nigeria. The Diagnostic Report examines the political, legal, and institutional environment for disclosure in PPPs. Based on a gap assessment exercise with key political, legal, institutional, and process findings benchmarked against the World Bank Framework, the Diagnostic Report makes specific recommendations to improve disclosure. The recommendations include a suggested enhanced framework for disclosure of PPPs applicable to all federal government projects in Nigeria, and an extended disclosure framework (beyond PPPs) for three types of investments by the Nigeria Sovereign Investment Authority (NSIA).